Ternary synergetic reinforced carbon quantum dot as well as preparation method and application thereof
Triple-coordinated carbon quantum dots prepared through hydrothermal reactions of citric acid, methionine and copper sources solve the problems of existing antibiotic resistance and environmental impact, and provide efficient and environmentally friendly antibacterial agents, which significantly improves the Antibacterial properties and scope of application.
Patent Information
- Application Number
- CN202411426415.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
Existing antibiotics have caused bacterial resistance problems in the face of rapidly evolving viruses and abuse, lack of effective new antibacterial agents, and traditional antibacterial materials have biotoxicity and environmental impacts.
The hydrothermal reaction of citric acid, methionine and copper sources is carried out to prepare ternary synergistically strengthened carbon quantum dots. The active sites and copper ions are coordinated on the surface of carbon quantum dots through nitrogen and sulfur atoms, forming active sites and copper ions to form excellent water solubility and Antibacterial agent with antibacterial properties.
It has achieved convenient operation, low cost and environmentally friendly antibacterial agents, significantly improved antibacterial performance, reduced bacterial resistance and growth rate, and is suitable for industries such as biology, medicine, and chemical industry.
Smart Images

Figure CN119302311A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of antibacterial agents, and specifically relates to a ternary synergistically enhanced carbon quantum dot and a preparation method and application thereof. Background Art
[0002] Pathogenic microorganisms such as bacteria and viruses have a huge impact on human health. How to quickly and effectively eliminate pathogenic microorganisms is related to the health and development of human society. Antibiotics, as one of the greatest inventions of mankind in the 20th century, have saved countless lives that were endangered by bacterial and viral infections. However, due to the rapid evolution of viruses and the abuse of antibiotics, more and more bacteria have developed drug resistance. The shortcomings of antibiotics have also gradually emerged, such as their own biological toxicity, accelerating the development of pathogens to develop drug resistance, etc. Therefore, the development of new antibacterial agents is imminent.
[0003] Carbon quantum dots not only have the advantages of low toxicity and good biocompatibility of carbon materials, but also have incomparable advantages such as excitation-dependent fluorescence emission, tunable fluorescence surface groups, adjustable luminescence range, large two-photon absorption cross section, good photostability, no light flickering, easy functionalization, low cost, easy large-scale synthesis, and environmental friendliness. They show great advantages and broad application prospects in the biological field. Therefore, it is a very meaningful study to explore the antibacterial properties and antibacterial mechanisms of carbon quantum dots. Carbon quantum dots are expected to replace traditional antibacterial materials for the treatment of bacterial infections. Summary of the invention
[0004] The main purpose of the present invention is to provide a ternary synergistically reinforced carbon quantum dots and a preparation method and application thereof to overcome the deficiencies of the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] An embodiment of the present invention provides a method for preparing ternary synergistically reinforced carbon quantum dots, which comprises: subjecting a mixed reaction system comprising at least citric acid and / or citric acid derivatives, methionine and / or methionine derivatives, and a copper source to a hydrothermal reaction at 180 to 300° C. to obtain ternary synergistically reinforced carbon quantum dots.
[0007] The embodiment of the present invention also provides ternary synergistically strengthened carbon quantum dots prepared by the aforementioned preparation method, wherein the nitrogen atoms and sulfur atoms in the ternary synergistically strengthened carbon quantum dots form active sites on the surface of the carbon quantum dots and form coordination with copper ions.
[0008] The embodiment of the present invention also provides the use of the aforementioned ternary synergistically reinforced carbon quantum dots in the preparation of biological antibacterial preparations.
[0009] The embodiment of the present invention further provides a biological antibacterial preparation, which at least includes the aforementioned ternary synergistically reinforced carbon quantum dots.
[0010] The embodiment of the present invention also provides a method for using an antibacterial agent, which comprises: dissolving the aforementioned ternary synergistically reinforced carbon quantum dots as an antibacterial agent in water, and then spraying or applying it on an area where bacteria are distributed or around it.
[0011] Compared with the prior art, the present invention has the following beneficial effects:
[0012] (1) The method for ternary synergistic strengthening of carbon quantum dots provided by the present invention has the advantages of convenient operation, low cost and environmental protection;
[0013] (2) The ternary synergistically reinforced carbon quantum dots provided by the present invention have excellent water solubility and antibacterial properties. Nitrogen and sulfur atoms enter the carbon quantum dots to form active sites on their surface and chemically coordinate with metal copper ions, giving full play to the synergistic antibacterial properties of carbon quantum dots and metal copper ions; at the same time, good water solubility effectively improves the dispersibility of the antibacterial agent in an aqueous environment;
[0014] (3) The present invention prepares an antibacterial agent by hydrothermal reaction of citric acid and / or its derivatives, methionine and / or its derivatives, copper gluconate and a solvent. The antibacterial agent has good water solubility and excellent antibacterial performance, and can also be used in the biological, pharmaceutical, chemical, shipbuilding, petroleum, marine and other industries. The antibacterial agent of the present invention is used in biomedicine to improve the antibacterial effect and reduce the drug resistance of bacteria. It is also used in a bacterial environment to reduce the growth rate of bacteria. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 This is a schematic diagram of the preparation process of ternary synergistically reinforced carbon quantum dots in a typical embodiment of the present invention;
[0017] Figure 2 This is a solubility picture of the ternary synergistically enhanced carbon quantum dots prepared in Example 1 of the present invention;
[0018] Figure 3 This is a high-resolution transmission image of the ternary synergistically reinforced carbon quantum dots prepared in Example 1 of the present invention;
[0019] Figure 4 This is a graph showing the antibacterial rate of blank carbon quantum dots against Staphylococcus aureus and Escherichia coli in Comparative Example 1 of the present invention;
[0020] Figure 5 This is a graph showing the antibacterial rate of blank carbon quantum dots against Streptococcus and Pneumococcus in Comparative Example 2 of the present invention;
[0021] Figure 6 This is a graph showing the antibacterial rate of blank carbon quantum dots against anaerobic bacteria and Pseudomonas aeruginosa in Comparative Example 3 of the present invention;
[0022] Figure 7 This is a graph showing the antibacterial rate of nitrogen-sulfur-doped carbon quantum dots against Staphylococcus aureus and Escherichia coli in Comparative Example 4 of the present invention;
[0023] Figure 8 This is a graph showing the antibacterial rate of copper-doped carbon quantum dots against Staphylococcus aureus and Escherichia coli in Comparative Example 5 of the present invention;
[0024] Fig. 9 This is a graph showing the antibacterial rate of nitrogen-sulfur-copper-doped carbon quantum dots against Staphylococcus aureus and Escherichia coli in Comparative Example 6 of the present invention;
[0025] Fig.10 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 1 of the present invention against Staphylococcus aureus and Escherichia coli;
[0026] Fig.11 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 2 of the present invention against Streptococcus and Pneumococcus;
[0027] Fig.12 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 3 of the present invention against anaerobic bacteria and Pseudomonas aeruginosa;
[0028] Fig.13 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 4 of the present invention against Staphylococcus aureus and Escherichia coli;
[0029] Fig.14 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 5 of the present invention against Staphylococcus aureus and Escherichia coli;
[0030] Fig.15 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 6 of the present invention against Staphylococcus aureus and Escherichia coli;
[0031] Fig.16 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 7 of the present invention against Staphylococcus aureus and Escherichia coli;
[0032] Fig.17 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 8 of the present invention against Staphylococcus aureus and Escherichia coli;
[0033] Fig.18This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 9 of the present invention against Staphylococcus aureus and Escherichia coli;
[0034] Fig.19 This is a graph showing the antibacterial rate of the ternary synergistically enhanced carbon quantum dots prepared in Example 10 of the present invention against Staphylococcus aureus and Escherichia coli. DETAILED DESCRIPTION
[0035] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Specifically, as one aspect of the technical solution of the present invention, a method for preparing ternary synergistically reinforced carbon quantum dots involves: subjecting a mixed reaction system comprising at least citric acid and / or citric acid derivatives, methionine and / or methionine derivatives, and a copper source to a hydrothermal reaction at 180 to 300° C. to obtain ternary synergistically reinforced carbon quantum dots.
[0037] The schematic diagram of the preparation process of the ternary synergistically strengthened carbon quantum dots in the present invention is as follows Figure 1 shown.
[0038] In some preferred embodiments, the preparation method specifically includes: mixing citric acid and / or citric acid derivatives, methionine and / or methionine derivatives, a copper source and a solvent and performing a hydrothermal reaction, then adjusting the pH value of the obtained solution to 2.5-6.5 with acetic acid and ammonia water, and then stirring, ultrasonicating, centrifuging, filtering, dialysis, and drying to obtain ternary synergistically reinforced carbon quantum dots.
[0039] Further, the citric acid derivative includes ammonium citrate and / or sodium citrate, but is not limited thereto.
[0040] Further, the methionine derivatives include N-methyl-D-methionine and / or N-methyl-L-methionine, but are not limited thereto.
[0041] Further, the copper source includes any one or more combinations of copper gluconate, copper citrate, and copper acetate, but is not limited thereto.
[0042] Furthermore, the solvent includes any one or more combinations of water, acetic acid, and aqueous ammonia, but is not limited thereto.
[0043] Furthermore, the mass ratio of the copper source to citric acid and / or citric acid derivatives is 1:100 to 20:100.
[0044] Furthermore, the mass ratio of the methionine and / or methionine derivatives to the citric acid and / or citric acid derivatives is 1:100 to 20:100.
[0045] Furthermore, the hydrothermal reaction time is 2 to 10 hours.
[0046] Furthermore, the stirring treatment time is 10 to 30 minutes.
[0047] Furthermore, the ultrasonic treatment time is 10 to 30 minutes.
[0048] Furthermore, the rotation speed of the centrifugal treatment is 8000-16000 r / min, and the time is 10-30 min.
[0049] Furthermore, the filtration treatment is vacuum filtration, and the number of vacuum filtration is 2 to 4 times.
[0050] Furthermore, the molecular weight of the dialysis bag used in the dialysis treatment is 1 to 5 KD.
[0051] Furthermore, the drying process is carried out at a temperature of 65 to 85° C. and for a time of 20 to 60 hours.
[0052] Another aspect of an embodiment of the present invention further provides ternary synergistically reinforced carbon quantum dots prepared by the aforementioned preparation method, wherein the nitrogen atoms and sulfur atoms in the ternary synergistically reinforced carbon quantum dots form active sites on the surface of the carbon quantum dots and form coordination with copper ions.
[0053] Furthermore, the constituent elements of the ternary synergistically strengthened carbon quantum dots include Cu, S, N, C, H and O.
[0054] Furthermore, the particle size of the ternary synergistically reinforced carbon quantum dots is 2 to 20 nm.
[0055] Furthermore, the solubility of the ternary synergistically reinforced carbon quantum dots in water is 10 to 100 mg / mL.
[0056] Furthermore, the content of nitrogen atoms in the ternary synergistically strengthened carbon quantum dots is 0.5-10wt%, the content of sulfur atoms is 0.5-10wt%, and the content of copper ions is 1.0-10wt%.
[0057] Another aspect of the embodiments of the present invention further provides the use of the aforementioned ternary synergistically reinforced carbon quantum dots in the preparation of biological antibacterial preparations.
[0058] Furthermore, the bacteria inhibited and / or killed by the biological antibacterial preparation include any one or more combinations of Streptococcus, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus, but are not limited thereto.
[0059] The experimental results of the present invention show that after Escherichia coli and Staphylococcus aureus were grown in the ternary synergistically enhanced carbon quantum dots for 24 hours, the inhibition rate was still above 92% compared with that in the solution without the addition of ternary synergistically enhanced carbon quantum dots, thus showing excellent antibacterial properties. Compared with the solution without carbon quantum dots, the antibacterial rate was increased by 1 to 3 times.
[0060] After 24 hours of growth in the ternary synergistically enhanced carbon quantum dots, the inhibition rate of streptococci and pneumococci can still reach more than 92% compared with the solution without the addition of ternary synergistically enhanced carbon quantum dots. Compared with the solution without carbon quantum dots, the inhibition rate is increased by 1 to 4 times.
[0061] After 24 hours of growth in the ternary synergistically enhanced carbon quantum dots, the inhibition rate of anaerobic bacteria and Pseudomonas aeruginosa was still above 92% compared with that in the solution without the addition of ternary synergistically enhanced carbon quantum dots. Compared with the solution without carbon quantum dots, the inhibition rate was increased by 2 to 6 times.
[0062] Another aspect of an embodiment of the present invention further provides a biological antibacterial preparation, which at least includes the aforementioned ternary synergistically reinforced carbon quantum dots.
[0063] Another aspect of an embodiment of the present invention further provides a method for using an antibacterial agent, which comprises: dissolving the aforementioned ternary synergistically reinforced carbon quantum dots as an antibacterial agent in water, and then spraying or coating them around the bacteria.
[0064] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0065] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0066] Comparative Example 1
[0067] The preparation process is:
[0068] (1) Take 2g of citric acid and dissolve it in 60mL of deionized water, then transfer it to a single-necked flask and react it at 200℃ for 6h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10min, and then ultrasonicate it for 10min, then filter and centrifuge it. The speed during the centrifugation is 10000r / min, and then dialyze it. The molecular weight of the dialysis bag is 2KD. Finally, put the dialysate into a vacuum drying oven for drying at 80℃ to obtain citric acid carbon quantum dots.
[0069] (2) Then, a certain amount of citric acid carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solution. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of citric acid carbon quantum dots was measured by plate count method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria. Figure 4 shown.
[0070] Comparative Example 2
[0071] The preparation process is:
[0072] (1) Take 2g of citric acid and dissolve it in 60mL of deionized water, then transfer it to a single-necked flask and react it at 200℃ for 6h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10min, and then ultrasonicate it for 10min, then filter and centrifuge it. The speed during the centrifugation is 10000r / min, and then dialyze it. The molecular weight of the dialysis bag is 2KD. Finally, put the dialysate into a vacuum drying oven for drying at 80℃ to obtain citric acid carbon quantum dots.
[0073] (2) Then, a certain amount of citric acid carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. The streptococcus and pneumococcus solutions were mixed with the above carbon quantum dot solutions. After culturing for 24 hours, the number of streptococci and pneumococci under different concentrations of citric acid carbon quantum dots was measured by plate counting method, and the inhibition rate of bacteria was obtained by comparing the free growth of bacteria. Figure 5 shown.
[0074] Comparative Example 3
[0075] The preparation process is:
[0076] (1) Take 2g of citric acid and dissolve it in 60mL of deionized water, then transfer it to a single-necked flask and react it at 200℃ for 6h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10min, and then ultrasonicate it for 10min, then filter and centrifuge it. The speed during the centrifugation is 10000r / min, and then dialyze it. The molecular weight of the dialysis bag is 2KD. Finally, put the dialysate into a vacuum drying oven for drying at 80℃ to obtain citric acid carbon quantum dots.
[0077] (2) Then, a certain amount of citric acid carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. The anaerobic bacteria and Pseudomonas aeruginosa solutions were mixed with the above carbon quantum dot solutions. After culturing for 24 hours, the plate count method was used to measure the changes in the number of anaerobic bacteria and Pseudomonas aeruginosa under different concentrations of citric acid carbon quantum dots, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Figure 6 shown.
[0078] Comparative Example 4
[0079] The preparation process is:
[0080] (1) Take 2g of citric acid and 0.2g of methionine and dissolve them in 60mL of deionized water, then transfer them to a single-necked flask and react them at 200°C for 6h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10min, and then ultrasonicate it for 10min, then filter and centrifuge it. The speed during the centrifugation is 10000r / min, and then dialyze it. The molecular weight of the dialysis bag is 2KD. Finally, put the dialysate into a vacuum drying oven for drying at 80°C to obtain citric acid carbon quantum dots.
[0081] (2) Then, a certain amount of citric acid carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solution. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of citric acid carbon quantum dots was measured by plate count method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria. Figure 7 shown.
[0082] Comparative Example 5
[0083] The preparation process is:
[0084] (1) Take 2g of citric acid and 0.2g of copper gluconate and dissolve them in 60mL of deionized water, then transfer them to a single-necked flask and react them at 200°C for 6h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10min, and then ultrasonicate it for 10min, then filter and centrifuge it. The speed during the centrifugation is 10000r / min, and then dialyze it. The molecular weight of the dialysis bag is 2KD. Finally, put the dialysate into a vacuum drying oven for drying at 80°C to obtain citric acid carbon quantum dots.
[0085] (2) Then, a certain amount of citric acid carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solution. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of citric acid carbon quantum dots was measured by plate count method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria. Figure 8 shown.
[0086] Comparative Example 6
[0087] The preparation process is:
[0088] (1) Take 0.2g of methionine and 0.2g of copper gluconate and dissolve them in 60mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10min, and then ultrasonicate it for 10min, then filter and centrifuge it. The speed during the centrifugation is 10000r / min. Then dialyze it, and the molecular weight of the dialysis bag is 2KD. Finally, put the dialysate into a vacuum drying oven and dry it at 80°C to obtain methionine-based carbon quantum dots.
[0089] (2) Then, a certain amount of methionine-based carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After culturing for 24 hours, the number of Staphylococcus aureus and Escherichia coli under different concentrations of methionine-based carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig. 9 shown.
[0090] Example 1
[0091] The preparation process of antibacterial agent is as follows:
[0092] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0093] (2) Then, dialysis treatment was performed, and the molecular weight of the dialysis bag was 2KD. Finally, the dialysate was placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically enhanced carbon quantum dots. The solubility is shown in 2 (it can be seen that the ternary synergistically enhanced carbon quantum dots prepared in this example have good water solubility), and the morphology is shown in Figure 3 shown.
[0094] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.10 shown.
[0095] Example 2
[0096] The preparation process of antibacterial agent is as follows:
[0097] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 1 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0098] (2) Then, dialysis treatment was performed, and the molecular weight of the dialysis bag was 2KD. Finally, the dialysate was placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically reinforced carbon quantum dots. The solubility is shown in 2, and the morphology is shown in Figure 3 shown.
[0099] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. The streptococcus and pneumococcus solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of streptococci and pneumococci under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the inhibition rate of bacteria was obtained by comparing the free growth of bacteria. Fig.11 shown.
[0100] Example 3
[0101] The preparation process of antibacterial agent is as follows:
[0102] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0103] (2) Then, dialysis treatment was performed, and the molecular weight of the dialysis bag was 2KD. Finally, the dialysate was placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically reinforced carbon quantum dots. The solubility is shown in 2, and the morphology is shown in Figure 3 shown.
[0104] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. The anaerobic bacteria and Pseudomonas aeruginosa solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of anaerobic bacteria and Pseudomonas aeruginosa under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.12 shown.
[0105] Example 4
[0106] The preparation process of antibacterial agent is as follows:
[0107] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.1 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0108] (2) Afterwards, dialysis treatment is performed, and the molecular weight of the dialysis bag is 2KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically reinforced carbon quantum dots.
[0109] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.13 shown.
[0110] Example 5
[0111] The preparation process of antibacterial agent is as follows:
[0112] (1) Take 2 g of citric acid, 0.1 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0113] (2) Afterwards, dialysis treatment is performed, and the molecular weight of the dialysis bag is 2KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically reinforced carbon quantum dots.
[0114] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.14 shown.
[0115] Example 6
[0116] The preparation process of antibacterial agent is as follows:
[0117] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 240°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0118] (2) Afterwards, dialysis treatment is performed, and the molecular weight of the dialysis bag is 2KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically reinforced carbon quantum dots.
[0119] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.15 shown.
[0120] Example 7
[0121] The preparation process of antibacterial agent is as follows:
[0122] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 2 h. After the reaction is completed, adjust the pH value of the solution to 4, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 10000 r / min.
[0123] (2) Afterwards, dialysis treatment is performed, and the molecular weight of the dialysis bag is 2KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 80°C to obtain ternary synergistically reinforced carbon quantum dots.
[0124] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.16 shown.
[0125] Example 8
[0126] The preparation process of antibacterial agent is as follows:
[0127] (1) Take 2 g of citric acid, 0.2 g of methionine, and 0.2 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 200°C for 6 h. After the reaction is completed, adjust the pH value of the solution to 6, stir the solution for 15 min, and then ultrasonicate it for 15 min, then filter and centrifuge it. The speed during the centrifugation is 12000 r / min.
[0128] (2) Afterwards, dialysis treatment is performed, and the molecular weight of the dialysis bag is 3KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 75°C to obtain ternary synergistically reinforced carbon quantum dots.
[0129] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.17 shown.
[0130] Example 9
[0131] (1) Take 2 g of ammonium citrate, 0.02 g of N-methyl-D-methionine, and 0.02 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 180°C for 10 h. After the reaction is completed, adjust the pH value of the solution to 6.5, stir the solution for 30 min, and then ultrasonicate it for 30 min, then filter and centrifuge it. The speed during the centrifugation is 16000 r / min.
[0132] (2) Afterwards, dialysis treatment is performed, and the molecular weight of the dialysis bag is 1KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 85° C. to obtain ternary synergistically reinforced carbon quantum dots.
[0133] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.18 shown.
[0134] Example 10
[0135] (1) Take 2 g of sodium citrate, 0.4 g of N-methyl-L-methionine, and 0.4 g of copper gluconate and dissolve them in 60 mL of deionized water, then transfer them to a single-necked flask and react at 300°C for 2 h. After the reaction is completed, adjust the pH value of the solution to 2.5, stir the solution for 10 min, and then ultrasonicate it for 10 min, then filter and centrifuge it. The speed during the centrifugation is 8000 r / min.
[0136] (2) Then, dialysis treatment is performed, and the molecular weight of the dialysis bag is 5KD. Finally, the dialysate is placed in a vacuum drying oven for drying at a temperature of 85° C. to obtain ternary synergistically reinforced carbon quantum dots.
[0137] (3) Then, a certain amount of ternary synergistically enhanced carbon quantum dots was added to deionized water to prepare solutions with concentrations of 10, 20, 30, and 40 mg / L. Staphylococcus aureus and Escherichia coli solutions were mixed with the above carbon quantum dot solutions. After 24 hours of culture, the number of Staphylococcus aureus and Escherichia coli under different concentrations of ternary synergistically enhanced carbon quantum dots was measured by plate counting method, and the bacterial inhibition rate was obtained by comparing the free growth of bacteria, such as Fig.19 shown.
[0138] The results show:
[0139] (1) The antibacterial rates of the carbon quantum dots prepared in Comparative Example 1, Comparative Example 4, Comparative Example 5, Comparative Example 6 and Example 1 against Staphylococcus aureus and Escherichia coli were statistically compared and found to be as follows: Figure 4 As shown, at concentrations of 10, 20, 30, and 40 mg / L, the inhibition rates of blank carbon quantum dots against Staphylococcus aureus were 21%, 26%, 29%, and 32%, respectively, and the inhibition rates against Escherichia coli were 24%, 29%, 33%, and 35%, respectively.
[0140] After nitrogen and sulfur doping, Figure 7 As shown, the inhibition rates of nitrogen-sulfur doped carbon quantum dots against Staphylococcus aureus were 51%, 58%, 64% and 72%, respectively, which were increased by 1.4, 1.23, 1.21 and 1.25 times, respectively; the inhibition rates against Escherichia coli were 48%, 57%, 62% and 69%, respectively, which were increased by 1.0, 0.96, 0.88 and 0.97 times, respectively.
[0141] After copper doping, Figure 8 As shown, the inhibition rates of copper-doped carbon quantum dots against Staphylococcus aureus were 58%, 66%, 72% and 79%, respectively, which were increased by 1.76, 1.54, 1.48 and 1.47 times, respectively; the inhibition rates against Escherichia coli were 52%, 63%, 69% and 75%, respectively, which were increased by 1.17, 1.17, 1.09 and 1.14 times, respectively.
[0142] After doping with nitrogen-sulfur copper in the absence of citric acid carbon source, Fig. 9 As shown, the inhibition rates of nitrogen, sulfur and copper synergistically enhanced carbon quantum dots against Staphylococcus aureus were 62%, 69%, 77% and 82%, respectively, which were increased by 1.95, 1.65, 1.66 and 1.56 times, respectively; the inhibition rates against Escherichia coli were 57%, 68%, 72% and 79%, respectively, which were increased by 1.38, 1.34, 1.18 and 1.25 times, respectively.
[0143] Using citric acid as the carbon source, after copper-nitrogen-sulfur synergistic strengthening, such as Fig.10As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, which were increased by 2.86, 2.38, 2.21 and 2.06 times, respectively; the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively, which were increased by 2.5, 2.14, 1.91 and 1.83 times, respectively.
[0144] (2) Comparing the antibacterial rates of the carbon quantum dots prepared in Comparative Example 2 and Example 2 against Streptococcus and Pneumococcus, it was found that Figure 5 As shown, at concentrations of 10, 20, 30, and 40 mg / L, the inhibition rates of blank carbon quantum dots against Streptococcus were 18%, 21%, 26%, and 28%, respectively, and the inhibition rates against Pneumococcus were 22%, 27%, 32%, and 36%, respectively.
[0145] After copper-nitrogen-sulfur synergistic strengthening, Fig.11 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Streptococcus were 76%, 85%, 90% and 96%, respectively, which were increased by 3.22, 3.05, 2.43 and 2.43 times, respectively; the inhibition rates against Pneumococcus were 72%, 83%, 89% and 95%, respectively, which were increased by 2.27, 2.07, 1.78 and 1.64 times, respectively.
[0146] (3) The antibacterial rates of the carbon quantum dots prepared in Comparative Example 3 and Example 3 against anaerobic bacteria and Pseudomonas aeruginosa were statistically analyzed and found to be as follows: Figure 6 As shown, at concentrations of 10, 20, 30, and 40 mg / L, the inhibition rates of blank carbon quantum dots against anaerobic bacteria were 15%, 19%, 26%, and 29%, respectively, and the inhibition rates against Pseudomonas aeruginosa were 12%, 18%, 24%, and 31%, respectively.
[0147] After copper-nitrogen-sulfur synergistic strengthening, Fig.12 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against anaerobic bacteria were 75%, 86%, 92% and 97%, respectively, which were increased by 4.0, 3.52, 2.54 and 2.34 times, respectively; the inhibition rates against Pseudomonas aeruginosa were 78%, 88%, 93% and 98%, respectively, which were increased by 5.5, 3.89, 2.88 and 2.16 times, respectively.
[0148] (4) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 4 against Staphylococcus aureus and Escherichia coli were statistically analyzed and found to be as follows: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0149] As the copper gluconate content decreases, Fig.13 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 72%, 81%, 88% and 93%, respectively, which were reduced by 9%, 7%, 5% and 5%, respectively; the inhibition rates against Escherichia coli were 74%, 83%, 89% and 94%, respectively, which were reduced by 10%, 8%, 10% and 5%, respectively.
[0150] (5) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 5 against Staphylococcus aureus and Escherichia coli were statistically analyzed and found to be as follows: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0151] As the methionine content decreases, Fig.14 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 68%, 77%, 83% and 92%, respectively, which were reduced by 13%, 11%, 10% and 6%, respectively; the inhibition rates against Escherichia coli were 76%, 81%, 86% and 93%, respectively, which were reduced by 8%, 10%, 10% and 6%, respectively.
[0152] (6) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 6 against Staphylococcus aureus and Escherichia coli were statistically analyzed and found to be as follows: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0153] As the reaction temperature increases, Fig.15 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 78%, 85%, 89% and 94%, respectively, which were reduced by 3%, 3%, 4% and 5%, respectively; the inhibition rates against Escherichia coli were 74%, 81%, 85% and 95%, respectively, which were reduced by 10%, 10%, 11% and 4%, respectively.
[0154] (7) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 7 against Staphylococcus aureus and Escherichia coli were statistically analyzed and found to be as follows: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0155] As the reaction time decreases, Fig.16As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 75%, 83%, 88% and 93%, respectively, which were reduced by 6%, 5%, 5% and 5%, respectively; the inhibition rates against Escherichia coli were 72%, 79%, 84% and 92%, respectively, which were reduced by 12%, 12%, 12% and 7%, respectively.
[0156] (8) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 8 against Staphylococcus aureus and Escherichia coli were statistically analyzed and found to be as follows: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0157] With the change of extraction parameters after reaction, e.g. Fig.17 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 72%, 79%, 85% and 96%, respectively, which were reduced by 9%, 9%, 8% and 2%, respectively; the inhibition rates against Escherichia coli were 75%, 83%, 91% and 97%, respectively, which were reduced by 9%, 8%, 5% and 2%, respectively.
[0158] (9) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 9 against Staphylococcus aureus and Escherichia coli were statistically analyzed and found to be as follows: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0159] As the reaction parameters change, such as Fig.18 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 69%, 75%, 81% and 89%, respectively, which were reduced by 12%, 13%, 12% and 10%, respectively; the inhibition rates against Escherichia coli were 65%, 74%, 83% and 87%, respectively, which were reduced by 19%, 17%, 13% and 12%, respectively.
[0160] (10) The antibacterial rates of the ternary synergistically enhanced carbon quantum dots prepared in Examples 1 and 10 against Staphylococcus aureus and Escherichia coli were statistically compared and found to be: Fig.10 As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 81%, 88%, 93% and 98%, respectively, and the inhibition rates against Escherichia coli were 84%, 91%, 96% and 99%, respectively.
[0161] As the reaction parameters change, such as Fig.19As shown, the inhibition rates of the ternary synergistically enhanced carbon quantum dots against Staphylococcus aureus were 66%, 74%, 82% and 87%, respectively, which were reduced by 15%, 14%, 11% and 11%, respectively; the inhibition rates against Escherichia coli were 67%, 76%, 81% and 85%, respectively, which were reduced by 17%, 15%, 15% and 14%, respectively.
[0162] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0163] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing ternary synergistically strengthened carbon quantum dots, characterized in that: include: A mixed reaction system containing at least citric acid and / or citric acid derivatives, methionine and / or methionine derivatives, and a copper source is subjected to a hydrothermal reaction at 180-300° C. to obtain ternary synergistically reinforced carbon quantum dots.
2. The preparation method according to claim 1, characterized in that: Specifically include: Citric acid and / or citric acid derivatives, methionine and / or methionine derivatives, a copper source and a solvent are mixed and subjected to a hydrothermal reaction. Acetic acid and ammonia water are then used to adjust the pH value of the obtained solution to 2.5-6.
5. The solution is then subjected to stirring, ultrasound, centrifugation, filtration, dialysis and drying treatments to obtain ternary synergistically reinforced carbon quantum dots.
3. The preparation method according to claim 2, characterized in that: The citric acid derivatives include ammonium citrate and / or sodium citrate; and / or, the methionine derivatives include N-methyl-D-methionine and / or N-methyl-L-methionine; And / or, the copper source includes any one or more combinations of copper gluconate, copper citrate, and copper acetate; And / or, the solvent includes any one or more combinations of water, acetic acid, and aqueous ammonia.
4. The preparation method according to claim 2, characterized in that: The mass ratio of the copper source to citric acid and / or citric acid derivative is 1:100 to 20:100; And / or, the mass ratio of methionine and / or methionine derivatives to citric acid and / or citric acid derivatives is 1:100 to 20:100; And / or, the hydrothermal reaction time is 2 to 10 hours.
5. The preparation method according to claim 2, characterized in that: The stirring time is 10 to 30 minutes; And / or, the ultrasonic treatment time is 10 to 30 minutes; And / or, the rotation speed of the centrifugal treatment is 8000-16000 r / min, and the time is 10-30 min; And / or, the filtration treatment is vacuum filtration, and the number of vacuum filtration is 2 to 4 times; And / or, the molecular weight of the dialysis bag used in the dialysis treatment is 1 to 5 KD; And / or, the drying process is carried out at a temperature of 65 to 85° C. and for a time of 20 to 60 hours.
6. The ternary synergistically reinforced carbon quantum dots prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The nitrogen atoms and sulfur atoms in the ternary synergistically strengthened carbon quantum dots form active sites on the surface of the carbon quantum dots and form coordination with the copper ions.
7. The ternary synergistically strengthened carbon quantum dots according to claim 6, characterized in that: The particle size of the ternary synergistically strengthened carbon quantum dots is 2 to 20 nm; And / or, the solubility of the ternary synergistically enhanced carbon quantum dots in water is 10 to 100 mg / mL; And / or, the content of nitrogen atoms in the ternary synergistically strengthened carbon quantum dots is 0.5-10wt%, the content of sulfur atoms is 0.5-10wt%, and the content of copper ions is 1.0-10wt%.
8. Use of the ternary synergistically reinforced carbon quantum dots according to claim 6 or 7 in the preparation of a biological antibacterial preparation; preferably, the bacteria inhibited and / or killed by the biological antibacterial preparation include any one or more combinations of Streptococcus, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus.
9. A biological antibacterial preparation, characterized in that: At least includes the ternary synergistically reinforced carbon quantum dots described in claim 6 or 7.
10. A method for using an antibacterial agent, characterized in that: include: The ternary synergistically reinforced carbon quantum dots as claimed in claim 6 or 7 as an antibacterial agent are dissolved in water and then sprayed or coated on an area where bacteria are distributed or around it.
Citation Information
Cited By
Preparation method and application of antibacterial red light dual-emission carbon quantum dots based on sodium ion doping
CN121913486A